Green nanocomposites from renewable resources: effect of plasticizer on the structure and material properties of clay-filled starch - Pandey, JK; Singh, RP (Starch-Starke, 2005)
Nanocomposites of starch were prepared via different addition sequences of plasticizer and clay by the solution method. The extent of dispersion of the filler was evaluated by wide angle X-ray diffractometry (WAXD) in the resulting composites. Thermal stability, mechanical properties and water absorption studies were conducted to measure the material properties whereas FT-IR spectroscopy was used to study the microdomain structure of composites. The sequence of addition of components (starch/plasticizer (glycerol)/clay) had a significant effect on the nature of composites formed and accordingly properties were altered. Glycerol and starch both have the tendency to penetrate into the silicate layers but penetration of glycerol is favored owing to its smaller molecule size. The filler dispersion becomes highly heterogeneous and the product becomes more brittle when starch was plasticized before filling with clay due to the formation of a bulky structure resulting from electrostatic attractions between starch and plasticizer. It was concluded that best mechanical properties can be obtained if plasticizer is added after mixing of clay in the starch matrix.
Keywords: clay-filled starch; effect of plasticizer; Nanocomposites; WAXD

In situ polymerization of ethylene with bis(imino)pyridine iron(II) catalysts supported on clay: the synthesis and characterization of polyethylene-clay nanocomposites - Ray, S; Galgali, G; Lele, Arundhati C.; Sivaram, S (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
Polyethylene-clay nanocomposites were synthesized by in situ polymerization with 2,6-bis[1-(2,6-diisopropylphenylimino)ethyl] pyridine iron(II) dichloride supported on a modified montmorillonite clay pretreated with methylaluminoxane (MAO). The catalysts and the obtained nanocomposites were examined with wide-angle X-ray scattering. The exfoliation of the clay was further established by transmission electron microscopy. Upon the treatment of the clay with MAO, there was an increase in the d-spacing of the clay galleries. No further increase in the d-spacing of the galleries was observed with the iron catalyst supported on the MAO-treated clay. The catalyst activity for ethylene polymerization was independent of the Al/Fe ratio. The exfoliation of the clay inside the polymer matrix depended on various parameters, such as the clay content, catalyst content, and Al/Fe ratio. The crystallinity percentage and crystallite size of the nanocomposites were affected by the degree of exfoliation of the clay. Moreover, when ethylene was polymerized with a mixture of the homogeneous iron(II) catalyst and clay, the degree of exfoliation was significantly lower than when the polymerization was performed with a preformed clay-supported catalyst. This observation suggested that in the supported catalyst, at least some of the active centers resided within the galleries of the clay. (C) 2004 Wiley Periodicals, Inc.
Keywords: clay; In situ polymerization; Nanocomposites; polyethylene (PE); TEM; WAXS

Overview on the degradability of polymer nanocomposites - Pandey, JK; Reddy, KR; Kumar, AP; Singh, RP (Polymer Degradation and Stability, 2005)
Polymer nanocomposites have attracted great attention world wide from both academic and industrial points of view. The material properties of polymers can be enhanced dramatically by incorporating layered silicates at fairly low concentrations. The durability of any material depends upon several factors e.g. light, heat, microwaves, mechanical abrasion etc. The study and the effect of these factors on the performance are essentially required to extend the application limits. The durability of polymer nanocomposites has been evaluated under different environments. The present review describes the durability of different polymer nanocomposites mainly under thermal- and photoageing. Biodegradable nanoeomposites of different polymers are also discussed briefly. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; Degradation; layered silicates; Nanocomposites; weathering

Crystallisation in polymer nanocomposites - Jog, Jyoti Prakash (Materials Science and Technology, 2006)
Polymer nanocomposites are of interest as they exhibit extraordinary properties compared with the base polymer. The second phase dispersed in the polymer matrix can be carbon nanotubes, semi-conducting inorganic nanoparticles or layer silicates such as clay. Crystallisation in these materials is also of great interest. Polymers exhibit structures at various scales (e.g. lamella, unit cell and spherulites) and the presence of a second phase has a profound effect on crystallisation. General trends observed include acceleration/retardation of crystallisation, changes in spherulite morphology and, in a few cases, changes in the crystal structure. All these observations relate to the presence of a micrometre scale second phase. However, when the dimensions of the second phase are close to the chain dimensions, the effects on crystallisation become particularly interesting. An attempt is made in the present review to address the effect of a nanoscale second phase on aspects such as isothermal and non-isothermal crystallisation, spherulite growth, phase transformation and polymorphism.
Keywords: clay; crystallisation; Nanocomposites; polymer matrix composites

Nanocomposites of polypropylene impact copolymer and organoclays: role of compatibilizers - Deenadayalan, E.; Vidhate, Shailesh; Lele, Ashish K. (Polymer International, 2006)
Nanocomposites of polypropylene impact copolymer and organoclays were prepared using different compatibilizers (polypropylene-graft-(maleic anhydride) (PPMA), polyethylene-graft-(maleic anhydride) (PEMA) and their mixture) and varying percentages of clay (3 and 6%) in an attempt to obtain balanced mechanical properties. The nanocomposites were prepared by melt compounding and test specimens were prepared by injection molding. Mechanical properties such as tensile, flexural and Izod impact strength are reported. The clay dispersion was investigated using wide-angle X-ray diffraction while the phase morphology was characterized using scanning electron microscopy. It is shown that the mechanical properties of the system with mixed PPMA and PEMA compatibilizers showed the best balance of mechanical properties among the nanocomposites explored. (C) 2006 Society of Chemical Industry.
Keywords: clay; compatibilizers; Nanocomposites; polypropylene

Preparation and characterization of novel hybrid of chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Biomedical Materials Research Part A, 2006)
The utilization of biopolymers and the development of organic-inorganic hybrids are ever increasing interest of material science researchers around the globe for various applications. The present attempt is intended to prepare nanocomposites of lactic acid grafted chitosan and layered silicates. Nanocomposites were prepared by dissolving chitosan and dispersing sodium montmorillonite in aqueous solution of L-lactic acid with subsequent heating and film casting. They were characterized by conventional techniques such as Fourier transform infrared spectroscopy, X-ray diffractometry, thermogravimetric analysis, energy dispersive X-ray spectroscopy, and elemental analysis. The results from polar optical and transmission electron microscopic measurements are also discussed. Sorption behavior of samples has been followed by measuring swelling degree and contact angle. The films have shown enhanced hydrophilicity when compared with polylactic acid (PLA). Issues on the interactions of polycationic chitosan with clay are also discussed. It is observed that nanocomposites are exhibiting better thermal and physical properties than neat chitosang-LA and PLA. (c) 2006 Wiley Periodicals, Inc.
Keywords: Chitosan; contact angle; graft copolymerization; Nanocomposites; polylactic acid; water absorption

Preparation and performance evaluation of EPDM nanocomposites under accelerated weathering - Rana, Sravendra; Tevtia, Amit K.; Kumar, Bijendra; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2006)
The degradability of ethylene propylene diene monomer (EPDM) nanocomposites, prepared from organically modified montmorillonite (CMMT), is studied under accelerated UV irradiation (lambda >= 290 nm) for different time intervals. The development of functional groups during degradation is monitored by FT-IR spectroscopy whereas, surface changes are studied by scanning electron microscopy (SEM). The effect of clay modifier and clay concentration on the degradability are studied. The degradation of neat polymer and composites taking place traditionally and an increase in carbonyl and hydroxyl groups are observed with irradiation time. Neat EPDM is found to be less degradable than nanocomposites. Degradation products, as seen by FT-IR in nanocomposites are found to be the same as in neat polymer but are generated at a faster rate. According to the experimental results, one can define that both ammonium ion and neat montmorillonite (MMT) accelerate the photo-oxidation of EPDM.
Keywords: carbonyl index; Degradation; EPDM; layered silicates; Nanocomposites; photooxidation

Assessing feasibility of polyarylate-clay nanocomposites towards improvement of gas selectivity - Bhole, Yogesh S.; Wanjale, Santosh D.; Kharul, Ulhas K.; Jog, Jyoti Prakash (Journal of Membrane Science, 2007)
Polymer-clay nanocomposites are well known to reduce the penetrant permeability by following tortuous path. Effects of such reduction in gas permeability on variation in selectivity of nanocomposites prepared using a high permeability polymer were examined. The polyarylate: poly (tetramethyl bisphenolA-iso/terephthalate) that exhibits high permeability and moderate selectivity was chosen for making nanocomposites with two organically modified clays (Cloisite 6A and 10A) by solution intercalation method. The nanocomposite formation for various clay loadings (3, 5 and 7% w/w) in polyarylate was ascertained by change in physical properties (X-ray diffraction, DMA, TEM). Behavior of solution viscosity and nanocomposite density indicated existence of polymer-clay layer interactions. As anticipated, though the gas permeability of pure gases, viz., He, N-2, CH4 and CO2 exhibited decrease, it was not monotonous. This decrease was more for larger gases (N-2, CH4 and CO2) in comparison to the decrease for smaller gas (He) permeability. This led to a decrease in CO2/N-2 and CO2/CH4 selectivities and increase in He/CO2 selectivity; while He/CH4 selectivity was increased substantially at 7% clay loading. This variation indicated feasibility of nanocomposites formation as a tool for improving selectivity of certain gas pairs. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Gas permeation; Nanocomposites; polyarylates; selectivity; solution intercalation

Influence of organic modification on mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Applied Polymer Science, 2007)
The influence of organic modifiers on intercalation extent, structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay nanocomposites were studied. Two different organic modifiers with varying hydrophobicity (single tallow versus ditallow) were investigated. The nanocomposites were prepared from melt processing method and characterized using wide angle X-ray diffraction, transmission electron microscopy, thermogravimetric analysis, differential scanning calorimetry (DSC), and tensile tests. Mechanical properties such as tensile modulus (E), break stress (sigma(brk)), and 0% break strain (epsilon(brk)) were determined for nanocomposites at various clay loadings. Extent of PMMA intercalation is sufficient and in the range 9-15 angstrom depending on organoclay and filler loading. Overall thermal stability of nanocomposites increases by 16-30 degrees C. The enhancement in T-g of nanocomposite is merely by 2-4 degrees C. With increase in clay loading, tensile modulus increases linearly while % break strain decreases. Break stress is found to increase till 4 wt % and further decreases at higher clay loadings. The overall improvement in thermal and mechanical properties was higher for the organoclay containing organic modifier with lower hydrophobicity and single tallow amine chemical structure. (c) 2007 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; structure; Thermal properties

Use of poly(o-toluidine)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel - Chaudhari, Sudeshna; Patil, P. P.; Mandale, A. B.; Patil, K. R.; Sainkar, S. R. (Journal of Applied Polymer Science, 2007)
This study explored the possibility of using poly(o-toluidine) (POT)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel in a chloride environment. POT/ZrO2 nanocomposite coatings were synthesized on steel substrates through an electrochemical route. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy. The performance of POT/ZrO2 nanocomposites as protective coatings against the corrosion of mild steel in aqueous 3 wt % NaCl was evaluated with the potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of this study demonstrate that POT/ZrO2 nanocomposite coatings provide better protection for mild steel against corrosion than pure POT coatings. The corrosion potential was about 0.312 V versus a saturated calomel electrode, more positive in aqueous 3 wt % NaCl for the nanocomposite-coated steel than the uncoated steel, and the corrosion rate of steel was reduced by a factor of almost 51. (c) 2007 Wiley Periodicals, Inc.
Keywords: Coatings; conjugated polymers; FTIR; Nanocomposites; synthesis

Dielectric relaxations in PVDF/BaTiO3 nanocomposites - Chanmal, Chetan; Jog, Jyoti Prakash (Express Polymer Letters, 2008)
The present work aims at the study of molecular relaxations in PVDF/BaTiO3 nanocomposites using broadband dielectric spectroscopy. The nanocomposites of PVDF with BaTiO3 ( 10-30% by wt%) are prepared using simple melt mixing method. In dielectric permittivity study, two relaxation processes are identified corresponding to the crystalline, glass transition in the PVDF/BaTiO3 nanocomposites. The peaks shift to higher frequencies as the temperature is increased. Electric modulus formalism is used to analyze the dielectric relaxations to overcome the conductivity effects at low frequencies. In M `' spectra two peaks are observed only at high temperature and low frequency whereas a single relaxation peak appears at low temperatures. The single relaxation peak appearing at low temperatures is the alpha(c) relaxation attributed to crystalline chain relaxation in PVDF and the second relaxation peak which appears only at high temperatures and at a frequency lower than alpha(c) relaxation is identified as MWS relaxation. The temperature dependence of alpha(c) relaxation and MWS relaxation follows Arrhenius type behavior.
Keywords: dielectric spectroscopy; Interfacial polarization; MWS relaxation; Nanocomposites

Effect of fuel and its concentration on the nature of Mn in Mn/CeO2 solid solutions prepared by solution combustion synthesis - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, Veda (Acta Materialia, 2008)
Nano and microcrystalline, Mn/CeO2 solid solutions (5 mol.% Mn) have been prepared by solution combustion synthesis using urea, glycine or polyethylene glycol (PEG) as fuel. The nature of the fuel and its concentration (fuel to metal mole ratio, F/M have a strong influence on the physical and chemical characteristics of the resulting Mn/CeO2 solid solutions. The variations in the physicochemical properties are attributed to differences in (i) the adiabatic/real flame temperature realized with these fuels at different F/M ratios; (ii) the sustenance of the temperature or the quenching effect of the fuel at higher F/M ratios; (iii) combustion or decomposition of the precursors as the main course of the reaction; and (iv) the generation of gaseous products during combustion. Since the addition of the fuel to the initial precursor solution does not change the pH of the medium, the differences in the type of Mn species formed are mainly attributed to the combustion process. (C) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; Mn-ceria; Nanocomposites; X-ray diffraction (XRD); X-ray photoelectron spectroscopy (XPS)

Effect of synthesis procedure on the structure and properties of palladium/polycarbonate nanocomposites - Valmikanathan, O. P.; Ostroverkhova, O.; Mulla, Imtiaz S.; Vijayamohanan, K.; Atre, S. V. (Polymer, 2008)
In this paper, we compare two procedures for the synthesis of palladium (Pd)/polycarbonate (PC) nanocomposites as well as their morphological, optical, thermal and electrical properties. Pd nanoclusters were produced by the reduction of palladium chloride using a variation of Brust's method. Discrete I'd nanoclusters of similar to 15 nm size were formed in the absence of PC in the reaction mixture (ex situ method) while agglomeration of Pd nanoclusters was noticed in the presence of PC in the reaction mixture (in situ method). Fourier transform infrared spectroscopy (FTIR) suggests nanoparticle-polymer interactions and polymer conformational changes in the in situ nanocomposite films. Even after having the same Pd content, the ex situ nanocomposites films were found to transmit more light than the in situ nanocomposites. The glass transition temperature (T-g), decreased by similar to 16 degrees C for both the ex situ and in situ samples. Thermogravimetric analysis (TGA) indicated that the presence of Pd nanoclusters significantly improved the thermal stability of the nanocomposites, as evidenced by the enhanced onset of degradation by similar to 20 degrees C and similar to 40 degrees C for the in situ and ex situ nanocomposites, respectively. The electrical conductivity measurement shows a dramatic difference between these nanocomposites with a significantly higher value for the in situ nanocomposite (resistivity = 2.1 X 10(5) Omega m) compared to the ex situ nanocomposite (resistivity = 7.2 x 10(13) Omega m). (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: in situ and ex situ syntheses; Morphology; Nanocomposites

Enhanced conversion efficiency in dye-sensitized solar cells based on ZnO bifunctional nanoflowers loaded with gold nanoparticles - Dhas, Vivek V.; Muduli, Subas; Lee, Wonjoo; Han, Sung-Hwan; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
The ZnO nanoflowers loaded with gold (Au) nanoparticles (NPs) are synthesized by a hydrothermal route using mixed precursors and controlled conditions. The dye-sensitized solar cells based on the ZnO nanoflowers with Au NPs show power conversion efficiency of 2.5%, which is considerably higher than that of ZnO nanoflowers without Au NPs. Detailed characterizations are performed, presented, and discussed.
Keywords: crystal growth from solution; Gold; II-VI semiconductors; Nanocomposites; Nanoparticles; solar cells; wide band gap semiconductors; zinc compounds

Molecular dynamics of copolyester/clay nanocomposites as investigated by viscoelastic and dielectric analysis - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Journal of Polymer Science Part B-Polymer Physics, 2008)
We have investigated the molecular dynamics of poly(ethylene glycol-co-cycloxeane-1,4-dimethanol terephthalate) (PETG) nanocomposites based on a organically modified layered silicate. Intercalated namocomposites were prepared by melt compounding technique as evidenced from the X-ray diffraction and transmission electron microscopy studies. Two relaxation processes were observed in pure PETG as well as in the nanocomposites. The low-temperature beta-process was assigned to the local motions of C=O polar groups and the alpha-process was due to the glass-rubber transition or the segmental relaxations associated with the polymer chain backbone. Presence of layered silicates accelerated alpha-relaxation dynamics in the nanocomposites accompanied by a depression in T(g) which was attributed to the reduced intermolecular cooperativity between intercalated polymers chains. Additionally, a direct comparison between the viscoelastic and dielectric studies shows excellent agreement between the accelerated alpha dynamics of the nanocomposites. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2539-2555, 2008
Keywords: clay; Dielectric relaxation; Nanocomposites; polyesters

New poly(phenylene oxide)/polystyrene blend nanocomposites with clay: intercalation, thermal and mechanical properties - Tiwari, Rajkiran R.; Khilar, Kartic C.; Natarajan, Upendra (Journal of Applied Polymer Science, 2008)
We present the first study and results on the preparation and characterization of montmorillonite clay filter based polymer blend nanocomposites of the miscible poly(phenylene oxide)/polystyrene blend. Intercalated nanocomposites, prepared by a melt-processing method with 2-6 wt % commercially available organically modified sodium montmorillonite, have been characterized with wide-angle X-ray diffraction, transmission electron microscopy analysis, thermal analysis (thermogravimetric analysis and differential scanning calorimetry), and mechanical tensile tests. We show that nanocomposites can be successfully prepared in a batch mixer at temperatures much below the conditions conventionally used for this blend without organic degradation. Thermal stability is enhanced by nanoscale hybrid formation. The level of intercalation (change in the d-spacing) does not change with the clay loading. Better dispersion of clay in the blend matrix has been observed at a low level of clay content. The nanocomposites show improved tensile modulus (by 31%) in comparison to the blend, whereas the tensile strength (stress at break) and elongation decrease in the presence of the filler with an increase in the clay loading. The Halpin-Tsai model is able to predict the modulus of the nanocomposites in very good agreement with the experimental data. (c) 2008 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; poly(phenylene oxide); Polystyrene; Thermal properties

Preparation and characterization of novel hybrid of chitosan-g-PDMS and sodium montmorrilonite - Depan, Dilip; Kumar, Bijandra; Singh, Raj Pal (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2008)
Preparation and properties of Chitosan (CS)-clay nanocomposites grafted with polydimethyl siloxane (PDMS) with different clay ratios are herein discussed. CS is intercalated into sodium montmorrilonite and PDMS is grafted onto CS under UV irradiation. Sample films of CS intercalated into clay and grafted with PDMS were prepared by solvent casting method with varying amount of nanoclay and PDMS. They were characterized by conventional techniques such as X-ray diffractometry, fourier transform infrared spectroscopy, C-13 NMR, thermo gravimetric analysis, and differential thermal analysis. Sorption behavior of samples has been followed by measuring swelling degree and issues on the interactions of biopolymers with clay are also discussed. The water absorption of composites films reduces with an increase in the amount of incorporated clay. This is due to the barrier formation in the form of cross-linking points, which prevents water permeation into CS. The amount of adsorbed water is more, when the amount of CS exceeds the amount of PDMS. This shows high water retention capacity of CS. (c) 2007 Wiley Periodicals, Inc.
Keywords: Chitosan; graft copolymerization; Nanocomposites; PDMS; water absorption

Thermal and mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites over a wide range of filler loading - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer International, 2008)
BACKGROUND: Poly(methyl methacrylate) (PMMA)-organoclay nanocomposites with octadecylammonium, ion-modified montmorillonite, prepared via melt processing, over a wide range of filler loading (2-16 wt%) were investigated in detail. These hybrids were characterized for their dispersion structure, and thermal and mechanical properties, such as tensile modulus (E). break stress (sigma(brk)), percent break strain (epsilon(brk)) and ductility(J), using wide-angle X-ray diffraction, transmission electron microscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and tensile and impact tests. RESULTS: Intercalated nanocomposites were formed even in the presence of 16 wt% clay (high loading) in PMMA matrix. PMMA intercalated into the galleries of the organically modified clay, with a change in d-spacing in the range 11-16 angstrom. TGA results showed improved thermal stability of the nanocomposites. The glass transition temperature (T-g) of the nanocomposites, from DSC measurements, was 2-3 degrees C higher than that of PMMA. The ultimate tensile strength and impact strength decreased with increasing clay fraction. Tensile modulus for the nanocomposites increased by a significant amount (113%) at the highest level of clay fraction (16 wt%) studied. CONCLUSION: We show for the first time the formation of intercalated PMMA nanocomposites with alkylammonium-modified clays at high clay loadings (> 15wt%). Tensile modulus increases linearly with clay fraction, and the enhancement in modulus is significant. A linear correlation between tensile strength and strainat-break is shown. Thermal properties are not affected appreciably. Organoclay can be dispersed well even at high clay fractions to form nanocomposites with superior bulk properties of practical interest. (c) 2007 Society of Chemical Industry.
Keywords: impact strength; mechanical properties; Nanocomposites; PMMA; Thermal properties

Cell proliferation and controlled drug release studies of nanohybrids based on chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Acta Biomaterialia, 2009)
The present paper reveals the potential uses of novel hybrids of chitosan-g-lactic acid and sodium montmorillonite (MMT) in controlled drug delivery and tissue engineering applications. The drug-loaded novel nanohybrid films and porous scaffolds have been prepared by solvent casting and freeze-drying of the grafted polymer solution, respectively. Sodium Ibuprofen was loaded into nanohybrids of chitosan-g-lactic acid/sodium montmorillonite (CS-g-LA/MMT). Grafting of lactic acid and the drug loading were characterized by Fourier transform infrared spectroscopy. Formation of intercalated nanocomposites was confirmed by X-ray diffraction. Mechanical properties measurements have shown improvement in modulus and strength with expense of elongation by MMT reinforcement. The nanohybrids were found to be stable regardless of pH of the medium. The cell proliferation profile also shows that prepared nanohybrids are biocompatible. MMT reinforcement was found to control the drug (Ibuprofen) release rate in phosphate buffer saline solution (pH 7.4). MMT clay is therefore a viable additive for formulating sustained drug delivery systems based on lactic acid grafted chitosan. (C) 2008 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Chitosan; clay; Controlled release; drug delivery systems; Nanocomposites

Nanoscale particles for polymer degradation and stabilization-trends and future perspectives - Kumar, Annamalai Pratheep; Depan, Dilip; Tomer, Namrata Singh; Singh, Raj Pal (Progress in Polymer Science, 2009)
The field of nanoscience and nanotechnology is extending the applications of physics, chemistry, biology, engineering and technology into previously unapproached infinitesimal length scales. The polymer-nanoparticles/nanocomposites have been the exponentially growing field of research for developing the materials in last few decades and have been mainly focusing on the structure-property relationships and their development. Since the polymer-nanocomposites have been the staple of modern polymer industry, their durability under various environmental conditions and degradability after their service life are also essential fields of research. Thus, this article is intended to review the status of worldwide research in this aspect. Among various nanoparticulates, clay minerals and carbon nanotubes are more often used in enhancing physical, mechanical and thermal properties of polymers. In very few systems, the nano particulates have been incorporated into polymer as `nano-additives' for both purposes: degradation and stabilization of polymers. The degradation and durability of polymers is reviewed in the presence of nanoparticles/nanocomposites under different environmental conditions. Nanoparticle-induced biodegradation of polymers is also discussed. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanotubes; clay; Degradation and stabilization; Nanocomposites; Nanoparticles; Polymer

Self assembled hydrophobic nanoclusters of poly(methylmethcrylate) embedded into polyvinyl alcohol based hydrophilic matrix: preparation and water sorption study - Shukla, Sandeep Kumar; Shaikh, A. Wasif; Gunari, Nikhil; Bajpai, A. K.; Kulkarni, R. A. (Journal of Applied Polymer Science, 2009)
Hydrophilic matrices containing nanosized Clusters of hydrophilic moieties have demonstrated potential applications in biomedical field. A novel hydrogel containing nanosized domains (20-35 nm) of hydrophobic moieties of poly(methyl methacrylate) (PMMA) was prepared by grafting crosslinked p ly(acrylic acid-co-methyl-methacrylate) chains onto polyvinyl alcohol (PVA) backbone using an efficient redox system. The graft copolymerization process was investigated to observe the influence of gel components on the kinetic parameters of grafting such as rate of grafting (R(g)), grafting yield (G(y)) and grafting efficiency (G(e)). The prepared graft nanohydrogel was evaluated for its water sorption potential under varying chemical composition of the gel and changing pH, temperature, and ionic strength of the swelling bath. The swelling process was also examined mechanistically and diffusion constants (D) of water molecules through the swellable nanohydrogel were also evaluated. (c) 2008 Wiley Periodicals, Inc. J ppl Polym Sci 111: 1300-1310, 2009
Keywords: graft copolymers; hydrophilic polymers; Nanocomposites; swelling

Synthesis of nickel-rubber nanocomposites and evaluation of their dielectric properties - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2009)
Nanocomposites based on natural rubber and nano-sized nickel were synthesized by incorporating nickel nanoparticles in a natural rubber matrix for various loadings of the filler. Structural, morphological, magnetic and mechanical properties of the composites were evaluated along with a detailed study of dielectric properties. It was found that nickel particles were uniformly distributed in the matrix without agglomeration resulting ill a magnetic nanocomposite. The elastic properties showed an improvement with increase in filler content but breaking stress and breaking strain were found to decrease. Dielectric permittivity was found to decrease with increase in frequency, and found to increase with increase in nickel loading. The decrease in permittivity with temperature is attributed to the high volume expansivity of rubber at elevated temperatures. Dielectric loss of blank rubber as well as the composites was found to increase with temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Dielectric relaxation; Interfacial polarization; Nanocomposites

Flexible microwave absorber based on nickel ferrite nanocomposite - Sunny, Vijutha; Kurian, Philip; Mohanan, P.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2010)
Flexible magnetic composite materials were prepared by incorporating precharacterized nickel ferrite nanoparticles in a natural rubber matrix. The complex dielectric permittivity and magnetic permeability of the composites were measured at different microwave frequencies using the cavity perturbation technique. A steady increase in dielectric permittivity was observed with increase in filler concentration. Maxwell-Garnett mixture equations were employed to model the effective permittivity and permeability of the composite. Reflection loss was estimated by employing the model of single layer absorber backed with a perfect conductor. Reflection loss minima of -5.9 dB at 3.2 GHz for 12 mm thick rubber ferrite composite sheet is obtained in the S-band while a loss up to -16 dB could be achieved at 9.5 GHz in the X-band. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cavity perturbation; Complex permeability; Complex permittivity; Microwave absorber; Nanocomposites; Nickel ferrite

Influence of structure of organic modifiers and polyurethane on the clay dispersion in nanocomposites via in situ polymerization - Rama, Mallikarjuna Shroff; Swaminathan, Sivaram (Journal of Applied Polymer Science, 2010)
Influence of polyurethane (PU) structure on the nature of PU/clay nanocomposite was studied using varying amounts of trimethylol propane (TMP) as branching agent. The effect of hydroxyl groups in the modifier of organoclays on the structure of PU/clay nanocomposites was studied. Nanocomposites were characterized using wide-angle X-ray diffraction measurements (WAXD) and transmission electron microscopy (TEM). The results show that formation of completely exfoliated and well dispersed polyurethane/clay nanocomposites via in situ polymerization, is facilitated by the presence of tethering groups on the clay surface and an ability to form branched and crosslinked structures. Incorporation of long alkyl chains in addition to tethering hydroxyl groups in the modifier structure of the clay did not significantly improve the compatibility of linear PU with the clay. Intercalated thermoplastic polyurethane/clay nanocomposites, prepared using poly(caprolactone diol) as soft segment and isophorone diisocyanate and 1,4-butanediol as hard segments show increase in storage tensile moduli at temperatures before glass transition temperature when functional groups capable of chemically reacting with the growing polymer chains are present in the clay modifier. This is indicative of improved interaction of the polymer with the clay surface when the modifier has larger number of hydroxyl groups. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 118: 1774-1786, 2010
Keywords: intercalation and exfoliation; Nanocomposites; organoclay; polyurethane

On the magnetic, mechanical and rheological properties of rubber-nickel nanocomposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Polymer Bulletin, 2010)
Rubber-nickel nanocomposites were synthesized by incorporating freshly prepared nanometric nickel particles in two different matrices namely natural rubber and neoprene rubber according to specific recipes for various loadings of nano nickel and the cure characteristics of these composites were evaluated. The maximum torque values register an increase with the increase in loading of nickel in both composites and this is attributed to the non-interacting nature of nickel nanoparticles with rubber matrices. The cure time of natural rubber composites decreases with increase in the content of nickel, and in neoprene rubber cure, time increases with increase in filler content. In natural rubber, the curing reaction seems to be activated by the presence of nickel particles. The magnetization studies of the composites reveal that the magnetic properties of nickel are retained in the composite samples. The elastic modulus of natural rubber and neoprene rubber are largely improved by the incorporation of nickel particles.
Keywords: Cure characteristics; Elastic modulus; magnetic properties; Nanocomposites

Synthesis and corrosion protection aspects of poly(o-toluidine)/CdO nanoparticle composite coatings on mild steel - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Journal of Coatings Technology and Research, 2010)
This study examines the possibility of using poly(o-toluidine)/CdO (POT-CdO) nanoparticle composite coating for corrosion protection of mild steel in chloride environment. The POT-CdO nanoparticle composite coating was synthesized on mild steel from aqueous tartrate solution containing CdO-nanoparticles (size similar to 18 nm) by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-Visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction measurements. The corrosion protection aspects of the resulting POT-CdO nanocomposite structure were investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of these investigations reveal that the POT-CdO nanoparticle composite acts as a protective coating on mild steel and reduces the corrosion rate of mild steel almost by factor of 70.
Keywords: CdO; Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Mild steel; Nanocomposites; Poly(o-toluidine)

Effect of tethering on the structure-property relationship of TPU-dual modified laponite clay nanocomposites prepared by ex-situ and in-situ techniques - Mishra, Ananta K.; Chattopadhyay, Santanu; Rajamohanan, P. R.; Nando, Golok B. (Polymer, 2011)
Novel Thermoplastic Polyurethane (TPU)-dual modified Laponite clay nanocomposites were prepared by ex-situ and in-situ techniques. Two types of modified clays used in this work differ from each other by the number of active functional groups (tethering). Modified nanoclays are characterized by FTIR, Solid State NMR, XRD and TGA. Structural differences in the modified clays lead to novel tubular, elliptical and spherically aggregated morphologies of clays together with the hard segments of TPU. Changes in such morphology result in the difference in segmental relaxation, mechanical and rheological properties of the nanocomposites. In-situ prepared nanocomposites register inferior properties as compared to their ex-situ counterparts. The percent improvement in tensile strength and elongation at break of the ex-situ prepared nanocomposites with the modified clay having lesser tethering are found to be 67% and 208%, respectively. Thermal stability is enhanced by 35 degrees C as compared to that of the neat TPU. (C) 2010 Published by Elsevier Ltd.
Keywords: Dual modification; Nanocomposites; Thermoplastic polyurethane

Efficiency and recycling capability of montmorillonite supported Fe-Ni bimetallic nanocomposites towards hexavalent chromium remediation - Kadu, Brijesh S.; Sathe, Yogesh D.; Ingle, Abhijit B.; Chikate, Rajeev C.; Patil, Kashinath R.; Rode, Chandrashekhar V. (Applied Catalysis B-Environmental, 2011)
The remediation of Cr(VI) from simulated water streams is investigated using Fe-Ni bimetallic nanoparticles (Fe-Ni NPs) and their nanocomposites prepared with montmorillonite (MMT) clay. These nanocomposites are characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) surface area analyses. XRD analysis revealed proper dispersion as well as intercalation of Fe-Ni NPs in the clay matrix. TEM of nanocomposites showed the presence of spherical particles having a size of 20-40 nm. Batch experiments with a 25 mg L(-1) Cr(VI) solution and 2 g L-1 Fe-Ni NPs exhibited complete reduction of Cr(VI) within 10 min that follows first order reaction kinetics. Amongst 25%, 50%, 75% in situ and loaded nanocomposites, 75% compositions possess better activity with enhanced reduction capacity below pH 4 due to generation of reactive H center dot species. XPS analysis of nanocomposites after Cr(VI) treatment suggested that reduction process occurs through Cr(111) formation followed by its subsequent reduction to Cr(0). Their potentiality towards reusage is established from the recycling experiments that revealed the order of efficiency as 75% in situ > Fe-Ni NPs > 75% loaded nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cr(VI) remediation; Iron-nickel bimetallics; Montmorillonite; Nanocomposites; Recycling

Influence of reactive compatibilization on the structure and properties of PP/LDH nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer International, 2011)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared by the direct melt intercalation method usingmaleic anhydride grafted polypropylene (PP-g-MAH) as a reactive compatibilizer. The compatibilization effects provided by PP-g-MAH in different weight fractions and their influence on the structure and properties of the final nanocomposites were investigated. The interactions and structural morphology of the nanocomposites were examined by Fourier transform infrared spectroscopy, X-ray diffraction and transmission electronmicroscopy. Thermal, mechanical and rheological properties of these nanocomposites were investigated as a function of compatibilizer concentration. The detailed morphological and X-ray diffraction results revealed that the degree of LDH dispersion increases as the amount of PP-g-MAH increases. Study of the linear viscoelastic properties showed that the storage modulus G' is very sensitive to the microstructure of the nanocomposite. The thermal properties of the nanocomposites were significantly influenced by the weight fraction of PP-g-MAH due to the shielding and nucleating effect of exfoliated layers. Both the tensile strength and modulus showed substantial improvements with increasing PP-g-MAH content, while the elongation at break substantially decreased, although the presence of PP-gMAH somewhat improves these values. The overall results showed that 10 wt% of compatibilizer is optimum to achieve nanocomposites with better performance. (C) 2011 Society of Chemical Industry
Keywords: compatibilization; layered double hydroxides; Nanocomposites; polypropylene; Rheology; thermomechanical properties

Magnetic and electric responsive hydrogel-magnetic nanocomposites for drug-delivery application - Reddy, N. Narayana; Mohan, Y. Murali; Varaprasad, K.; Ravindra, S.; Joy, Pattayil Alias; Raju, K. Mohana (Journal of Applied Polymer Science, 2011)
Magnetic and electrically responsive hydrogel networks were developed for drug-delivery applications. The hydrogel matrices were synthesized by the polymerization of acrylamide monomer in the presence of carboxymethylcellulose (CMC) or methylcellulose (MC) with N,N-methylenebisacrylamide, a crosslinker with the redox initiating system ammonium persulfate/tetramethylethylenediamine. The magnetic nanoparticles were generated throughout these hydrogel matrices by an in situ method by the incorporation of iron ions and their subsequent reduction with ammonia. A series of hydrogel-magnetic nanocomposites (HGMNCs) were developed with various CMC and MC compositions. The synthesized HGMNCs were characterized with spectral (Fourier transform infrared and ultraviolet-visible spectroscopy), X-ray diffraction, thermal, and microscopy methods. These HGMNCs contained iron oxide (Fe3O4) nanoparticles with an average particle size of about 22 nm, as observed by transmission electron microscopy. The dielectrical properties of the pure hydrogel (HG); the hydrogel loaded with iron ions, or the hydrogel iron-ion composite (HGIC); and the HGMNCs were measured. These results suggest that HGMNCs exhibited higher dielectric constants compared to HG and HGICs. The curcumin loading and release characteristics were also measured for HG, HGIC, and HGMNC systems. These data revealed that there was a sustained release of curcumin from HGMNCs because of the presence of magnetic nanoparticles in the hydrogel networks. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1364-1375, 2011
Keywords: hydrogels; magnetic polymers; Nanocomposites; nanoparticle; nanotechnology

Polystyrene/TiO2 composite electrospun fibers as fillers for poly(butylene succinate-co-adipate): Structure, morphology and properties - Neppalli, Ramesh; Causin, Valerio; Benetti, Edmondo Maria; Ray, Suprakas Sinha; Esposito, Antonella; Wanjale, Santosh; Birajdar, Mallinath S.; Saiter, Jean-Marc; Marigo, Antonio (European Polymer Journal, 2014)
In this work, composite polystyrene/titanium dioxide (PS/TiO2) electrospun fibers were used as a reinforcement for a poly(butylene succinate-co-adipate) (PBSA) matrix. The structure, morphology, mechanical properties and degradation behavior of such materials were investigated, finding that, as a function of their TiO2 content, the fibers exerted different effects. The main mechanism through which the fibers modified the structure and morphology of the polymer matrix is by altering its crystallization kinetics. The presence of TiO2 modified the roughness of the fibers and therefore affected the interfacial adhesion between the filler and the matrix. The modulus of PBSA was improved, even though the brittleness of the materials was increased by the presence of the fibers. Different amounts of TiO2 within the fibers allowed to tune the hydrolytic degradation rate of the composites. This paper shows the potential of using composite electrospun fibers as effective fillers for the preparation of polymer-based composites. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable polymers; Degradation; electrospinning; Morphology; Nanocomposites; Polycaprolactone

Mechanically stable thermally cross linked poly(acrylic acid)/reduced graphene oxide aerogels - Ha, Heonjoo; Shanmuganathan, Kadhiravan; Ellison, Christopher J. (ACS Applied Materials & Interfaces, 2015)
Graphene oxide (GO) aerogels, high porosity (>99%) low density (similar to 3-10 mg cm(-3)) porous materials with GO pore walls, are particularly attractive due to their lightweight, high surface area, and potential use in environmental remediation, superhydrophobic and superoleophilic materials, energy storage, etc. However, pure GO aerogels are generally weak and delicate which complicates their handling and potentially limits their commercial implementation. The focus of this work Vas to synthesize highly elastic, mechanically stable aerogels that are robust and easy to handle without substantially sacrificing their high porosity or low density. To overcome this challenge, a small amount of readily available and, thermally cross-linkable poly(acrylic acid) (PAA) was intermixed with GO to enhance the mechanical integrity Of the aerogel without disrupting other desirable characteristic properties. This method is a simple straightforward procedure that does not include multistep or complicated chemical reactions, and it produces aerogels with mass densities of about 4-6 mg cm(-3) and >99.6% porosity-that can reversibly support up to 10 000 times their weight with full recovery of their original volume. Finally; pressure sensing capabilities were demonstrated and their oil absorption capacities were measured to be around 120 g oil per g aerogel(-1) which highlights their potential Use in practical applications.
Keywords: aerogels; environmental remediation; graphene; Nanocomposites; poly(acrylic acid)

Synthesis of novel silica-polyimide nanocomposite films using aromatic-amino modified silica nanoparticles: mechanical, thermal and morphological investigations - Ghorpade, Ravindra V.; Rajan, C. R.; Chavan, Nayaku; Ponrathnam, S. (Express Polymer Letters, 2015)
Silica nanoparticles were modified with aromatic amino groups and modified-silica/polyimide composite films were prepared using them. 3,3!, 4,4!-Benzophenone tetracarboxylic dianhydride (BTDA) and 4,4!-oxydianiline (ODA) were used as precursors for polyimide matrix. The structures of the modified nanoparticles and hybrid nanocomposites were identified using Fourier Transform Infrared (FTIR) spectrometry. The hybrid composite films were evaluated for mechanical, thermal and morphological characteristics. Morphological results describe a uniform dispersion of silica particles in the polymer matrix. The thermal stability and mechanical properties of polyimide composite were improved, and the decomposition temperature was increased when the amount of silica nanoparticles was increased.
Keywords: hybrid polyimide composites; mechanical properties; Nanocomposites; nanoparticle modification; Thermal properties

3D interconnected porous graphene sheets loaded with cobalt oxide nanoparticles for lithium-ion battery anodes - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Energy Technology, 2016)
Nanomaterials with high surface-to-volume ratio and tunable electronic and optical properties have expanded their use in variety of applications, especially energy conversion and storage. Here we report on the synthesis of a cobalt oxide (Co3O4)/3D-interconnected porous graphene (PG) nanocomposite by using a simple solvothermal route and its application as a Li-ion battery anode. Among the different compositions investigated, the composite PG-600 (with 50% PG) showed a discharge capacity of 700mAhg(-1) at a current density of 500mAg(-1) and maintained 90% retention after 80cycles. The high surface area of the 3DPG sheets helps the Co3O4 nanoparticles to form a uniform dispersion on the surfaces. The increased surface area (accessibility) and electrical conductivity of the composite result in significant enhancement in the capacity, cycling stability, and rate capability than the native Co3O4 phase.
Keywords: Cobalt oxide; Energy storage; graphene; lithium-ion batteries; Nanocomposites

Biogenic green synthesis of monodispersed gum kondagogu (Cochlospermum gossypium) iron nanocomposite material and its application in germination and growth of mung bean (Vigna radiata) as a plant model - Raju, Dugyala; Mehta, Urmil J.; Beedu, Sashidhar Rao (IET Nanobiotechnology, 2016)
An eco-friendly green and one-pot synthesis of highly monodispersed iron (Fe) nanoparticles (NPs) by using a natural biopolymer, gum kondagogu (GK) as reducing and capping agent is proposed. The NPs synthesised were characterised by ultra-violet-visible spectroscopy, transmission electron microscopy, scanning electron microscopy and X-ray diffraction. As the concentration of gum and time increases, the intensity of NPs formation increased. The NPs were highly monodispersed with uniform circular shapes of 2-6 nm in size. The formed NPs were crystalline in nature which was confirmed by diffraction analysis. The conversion ratio of Fe ionic form to NPs was 21% which was quantified by inductively coupled plasma mass spectroscopy (ICP-MS). Fe is essential for plant growth and development. A study was conducted to examine the effect of these NPs on the growth of mung bean (Vigna radiata). The radical length and biomass was increased in seeds exposed to Fe NPs than the ions. The uptake of Fe NPs by the sprouts was also quantified by ICP-MS, in which Fe was more in mung bean seeds exposed to NPs. The -amylase activity was increased in the seeds exposed to NPs. The observed increase in the biomass by Fe NPs and seed germination may facilitate its application in the agriculture as an important cost-effective method for plant growth.
Keywords: alpha-amylase activity; Biogenic green synthesis; biological techniques; Biomass; Cochlospermum gossypium; diffraction analysis; enzymes; Fe; gum concentration; high-monodispersed iron nanoparticles; inductively coupled plasma mass spectroscopy; ionic-to-nanoparticle iron conversion ratio; iron; monodispersed gum kondagogu; monodispersed gum kondagogu iron nanocomposite material; mung bean germination; mung bean growth; Nanobiotechnology; Nanocomposites; nanoparticle formation; Nanoparticles; natural biopolymer; plant growth; plant model; scanning electron microscopy; size 2 nm to 6 nm; transmission electron microscopy; ultraviolet spectra; ultraviolet-visible spectroscopy; Vigna radiata; visible spectra; X-ray diffraction

Improved performance of microcapsules with polymer nanocomposite wall: preparation and characterization - Jagtap, Siddheshwar B.; Mohan, Muthu Subramanian; Shukla, Parshuram G. (Polymer, 2016)
Polyurea/clay nanocomposite microcapsules containing dimethyl phthalate (DMP) as a model compound were prepared by interfacial polymerization technique. Nanoclays namely, montmorillonite Na+ (MMT) and Laponite were incorporated into microcapsule wall and their effects on morphology, thermal properties and release of DMP from microcapsules were investigated. All microcapsules were characterized using scanning electron microscope (SEM), X-ray diffraction (XRD), transmission electron microscope (TEM), thermogravimetric analysis (TGA) and Fourier transform infrared (FTIR) spectroscopy. The present preparation process results in formation of polyurea/clay nanocomposite microcapsule wall with intercalated clay layered as evidenced by XRD and TEM. Nanocomposite microcapsules have shown significant reduction in release of DMP and change in release mechanism as compared to the pristine microcapsules. Nanocomposite microcapsules show good improvement in the fracture strength as compared to pristine microcapsules. The approach used herein is simple and can be adopted to many other polymeric microcapsule systems prepared by different microencapsulation techniques, requiring reduction in release rate and/or mechanism for several applications like pharmaceuticals, agrochemicals, industrially important chemicals, consumer products, etc. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Microcapsules; Nanoclay; Nanocomposites; Polyurea; Release mechanism

MoO3-rGO nanocomposites for electrochemical energy storage - Khandare, Lina; Late, Dattatray J. (Applied Surface Science, 2017)
We have synthesized the one dimensional (1D) MoO3 nanorods and MoO3-rGO nanocomposite by using sonochemical dispersion method at low temperature. The obtained products were characterized by using Raman spectroscopy, FT-IR, SEM, TEM and HR-TEM. We have demonstrated the electrochemical properties of MoO3 nanorods and MoO3-rGO nanocomposites. The specific capacitance for MoO3 nanorods and MoO3-rGO nanocomposite was calculated to be 3.3 F/g and 22.83 F/g at current density of 0.3 A/g respectively. The nanocomposite of MoO3-rGO shows the better electrochemical performance as compared to pristine MoO3 nanorods sample due to improvement in the conductivity. Our result suggests that the MoO3-rGO nanocomposites material has great potential for electrochemical energy storage and related applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Energy storage; Nanocomposites; Nanorods; Storage (materials); Temperature

Multifunctional inulin tethered silver-graphene quantum dots nanotheranostic module for pancreatic cancer therapy - Joshi, Preeti Nigam; Agawane, Sachin; Agawane, Sachin; Agawane, Sachin; Sarkar, Dhiman; Sarkar, Dhiman (Material Science and Engineering C- Materials for Biological Application, 2017)
Cancer nanotechnology is an emerging area of cancer diagnosis and therapy. Although considerable progress has been made for targeted drug delivery systems to deliver anticancer agents to particular site of interest, new nanomaterials are frequently being developed and explored for better drug delivery efficiency. In the present work, we have explored a novel nanoformulation based on silver-graphene quantum dots (Ag-GQDs) nanocomposite for its successful implementation for pancreatic cancer specific drug delivery in wistar rats. Carboxymethyl inulin (CMI); a modified variant of natural polysaccharide inulin is tethered with the nanocomposite via carbodiimide coupling to enhance the biocompatibility of nanoformulation. Experiments are performed to investigate the cytotoxicity reduction of silver nanoparticles after inulin tethering as well as anticancer efficacy of the system using 5-Fluorouracil (5-FU) as model drug. SEM, TEM, FT-IR, UV-vis, photoluminescence and anti proliferative assays (MTT) are performed for characterisation of the nanocomposite. Hyaluronic acid (HA) is conjugated as targeting moiety for CD-44 (cancer stem cell marker) to fabricate a complete targeted drug delivery vehicle specific for pancreatic cancer. In the present work two prime objectives were achieved; mitigation the toxicity of silver nanoparticles by inulin coating and it's in vivo application for pancreatic cancer. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: acid; Dextran; Drug-delivery; graphene quantum dots; Inulin; Nanocomposite; Nanocomposites; Nanoparticles; Pancreatic Cancer; Silver nanoparticle; Strategies; Systems; Targeted Drug Delivery

Biofilm formation to inhibition: role of zinc oxide-based nanoparticles - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Badiger, Manohar V.; Patel, Pratikshkumar R.; Thorat-Gadgil, Bhagyashi S.; Pandit, Abhay; Bohara, Raghvendra A. (Materials Science & Engineering C-Materials for Biological Applications, 2020)
Zinc oxide nanoparticles have received much attention worldwide as they possess unique properties like varied morphology, large surface area to volume ratio, potent antibacterial activity, and biocompatibility. Biofilm contains homogenous or heterogeneous microorganisms that remain enclosed in a matrix of an extracellular polymeric substance on biotic or abiotic surfaces. Bacterial biofilm formed on medical devices such as central venous catheters, urinary catheters, prosthetic joints, cardiovascular implantable devices, dental implants, contact lenses, intrauterine contraceptive devices and breast implants cause persistent infections. Such biofilm-associated infections in medical implants cause serious problems for public health and affect the function of medical implants. So, there is an urgent need for the use of an antimicrobial agent that will inhibit biofilm, including such antibiotic-resistant bacterial strains as bacteria, to develop multiple drug-resistances resulting in failure of the antibiotic's action. The antimicrobial agent used should be ideal in terms of biocompatibility, antimicrobial activity, stability at different environmental conditions, with less sensitivity to the development of resistance towards micro-organisms, safe for in vivo and in vitro use, and remain non-hazardous to the environment, etc. The first objective of the review discusses the insights into the formation of biofilm on a medical device with the current strategies to inhibit. The second purpose is to review the recent progress in ZnO- based nanostructure including composites for antibacterial and anti-biofilm activities. This will offer a new opportunity for the application of Zinc oxide-based material in the prevention of biofilm on the medical devices.
Keywords: antibacterial activity; Antibiofilm agent; Biocompatibility; Biofilm; Nanocomposites; ZnO nanoparticles

Critical organic modifier aliphatic tail length for the formation of poly(methyl methacrylate)-montmorillonite nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer Engineering and Science, 2020)
In this article, we report the influence of organic modifier structure (alkyl chain length C8-C20, single vs ditallow) and thereby, the effect of hydrophobicity on the structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay hybrids. Melt processed PMMA-clay hybrids were characterized using wide-angle X-ray diffraction, transmission electron microscopy, and differential scanning calorimetry. The organoclays having an alkyl chain length of more than 12 CH2 groups resulted in the formation of nanocomposites. The glass transition temperature (T-g) of PMMA increased in the presence of clay. The mean-field lattice model was used to predict the free energy for nanocomposite formation, which showed a reasonable match with the experimental results and provided a general guideline for the proper selection of polymer and organoclay (ie, organic modifier) to obtain nanocomposite. Tensile modulus showed maximum improvement of 58% for the nanocomposites compared to 9% improvement for the composites. Tensile modulus increased with increases in the alkyl chain length of the organic modifier and clay loading. The level of improvement for the tensile properties of nanocomposites prepared from primary and secondary ammonium-modified clay is the same as that obtained with the commercial organoclays.
Keywords: hybrid; mechanical properties; Montmorillonite; Nanocomposites; organoclay; poly(methyl methacrylate)

Controlling draw resonance during extrusion film casting of nanoclay filled linear low-density polyethylene: an experimental study and numerical linear stability analysis - Rokade, Dhammaraj; Chougale, Sanket; Patil, Prashant; Bhattacharjee, Tanushree; Gawande, Dnyaneshwar; Pol, Harshawardhan; Dhadwal, Renu (Journal of Plastic Film & Sheeting, 2021)
Commercially important extrusion film casting (EFC) processes for manufacturing plastic films or sheets are hampered by several instabilities that severely limits their productivity. In this research we focussed on one important instability: the draw resonance that occurs during the EFC process mainly under extensional flow conditions. Draw resonance is the sustained periodic oscillations in the film dimensions, notably film width and thickness, when the process operates beyond a critical draw ratio (CDR). In this research our goal was to reduce this draw resonance instability by incorporating well dispersed nanoclay fillers in a base polymeric resin (such as a linear low density polyethylene - LLDPE) to determine how these nanocomposite (NC) formulations can prevent or reduce the draw resonance defect. EFC experiments were conducted on the base resin and on the NC formulations under non-isothermal conditions to determine the onset of the draw resonance experimentally. Conventional linear stability analysis was performed to determine the onset of the draw resonance defect numerically. Numerical predictions for the onset of draw resonance were in qualitative agreement with our experimental data. Our results showed that incorporating appropriate nanoclay concentrations in a base polymeric resin indeed enhanced the EFC process stability for those polymer formulations and thus can have important economic implications for processors.
Keywords: Draw resonance; extensional strain hardening; Extrusion; Film; hydrodynamic interactions; Nanoclay; Nanocomposites; Polyethylene; Rheology; stability

Double encapsulation of liquid active compounds using nanoclay reinforced polyurea microcapsules - Aher, Yogeshwar P.; Torris, Arun; Adhikari, Benu; Shukla, Ravi; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2023)
In recent years, there has been growing interest in the double encapsulation of drugs, agrochemicals, and fragrances, aiming to achieve the highest encapsulation efficiency and preserve the activity of the encapsulated core over an extended duration. However, when active ingredients in liquid form are double encapsulated, preventing the rupture of primary microcapsules during the second encapsulation process and the leakage of the encapsulated core are major challenges. This report describes a method that utilizes polyurea and starch for successful double encapsulation of dimethyl phthalate (DMP), a liquid insect-repellent, as a model active component. We demonstrate that the incorporation of 3 wt% montmorillonite (MMT) nanoclay strengthens the polyurea wall of the primary microcapsule and prevents its rupture during double encapsulation with starch. This process facilitates the uniform distribution of polyurea microcapsules within the starch matrix and significantly improves the mechanical integrity of the nanocomposite microcapsules embedded in starch. The double-encapsulated system developed in this study significantly reduces the release rate of encapsulated DMP.
Keywords: Controlled release; Double encapsulation; Microcapsules; Microencapsulation; Nanocomposites; Starch matrix